Sustainability Strategies and Stakeholders' Influence in The Palm Oil Industry - Nurhayati Soleha (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to identify sustainability strategies and stakeholders’ influence in the Indonesian palm oil industry based on sustainability reports. We find that 14 companies have already disclosed their environmental, social, and economic information in their annual reports, and 6 companies published stand-alone sustainability reports for 2015 to 2018. Our study focuses on environmental and social strategies and excludes economic performance. The first findings, sustainability strategies based on sustainability reports in the palm oil companies are as follows: 1) sustainability policy commitment, 2) conservation management, 3) forest/plantation fire prevention, 4) waste management, 5) traceability supply chain, 6) sustainability certifications, 7) community development, 8) grievance management. Second, key stakeholders influence various sustainability strategies.